2019
DOI: 10.3174/ajnr.a6316
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Iodine Leakage on Dual-Energy CT as a Marker of Blood-Brain Barrier Permeability in Traumatic Hemorrhagic Contusions: Prediction of Surgical Intervention for Intracranial Pressure Management

Abstract: BACKGROUND AND PURPOSE: Hemorrhagic contusions are associated with iodine leakage. We aimed to identify quantitative iodine-based dual-energy CT variables that correlate with the type of intracranial pressure management. MATERIALS AND METHODS: Consecutive patients with contusions from May 2016 through January 2017 were retrospectively analyzed. Radiologists, blinded to the outcomes, evaluated CT variables from unenhanced admission and short-term follow-up head dualenergy CT scans obtained after contrast-enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…16 Quantitative iodine parameters, including stroke, trauma, metastases, tumors, and perfusion, have been widely used in clinical practice. 12,[17][18][19][20][21][22] Bonatti et al 12 examined patients with acute ischemic stroke undergoing MT with DECT and reported an absolute iodine concentration of .1.35 mg I/mL in the maximum apparent attenuation area, thereby achieving a sensitivity of 100% and specificity of 67.5% in predicting ICH development. Our study also showed a significant difference in iodine concentration in postprocedural DECT between the 2 groups with and without ICH development, with a cutoff value of 2.7 mg I/mL.…”
Section: Discussionmentioning
confidence: 99%
“…16 Quantitative iodine parameters, including stroke, trauma, metastases, tumors, and perfusion, have been widely used in clinical practice. 12,[17][18][19][20][21][22] Bonatti et al 12 examined patients with acute ischemic stroke undergoing MT with DECT and reported an absolute iodine concentration of .1.35 mg I/mL in the maximum apparent attenuation area, thereby achieving a sensitivity of 100% and specificity of 67.5% in predicting ICH development. Our study also showed a significant difference in iodine concentration in postprocedural DECT between the 2 groups with and without ICH development, with a cutoff value of 2.7 mg I/mL.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with traumatic parenchymal hemorrhage, iodine quantification methods within the hematoma as a measure of blood–brain barrier permeability have been found to be the best CT predictors of need for decompression craniectomy as well as short-term outcome measures and inpatient mortality. 67,68 However, these DECT techniques did not outperform simple Glasgow Coma Scale for outcome prediction, and future studies correcting for initial Glasgow Coma Scale with more long-term outcome measures are warranted to prospectively validate the prognostic potential of DECT in patients with traumatic brain injury.…”
Section: Cerebral Hemorrhagementioning
confidence: 99%